American-Asian- and African lineages of Zika virus induce differential pro-inflammatory and Interleukin 27-dependent antiviral responses in human monocytes (2023)
ABSTRACT: Zika virus (ZIKV) is an arbovirus that belongs to the Flaviviridae family and inflammatory responses play a critical role in ZIKV pathogenesis. As a first-line defense, monocytes are key components of innate immunity and host response to viruses. Monocytes are considered the earliest blood cell type to be infected by ZIKV and have been shown to be associated with ZIKV pathogenesis. The first ZIKV epidemic was reported in Africa and Asia although, it is less well known whether African- and Asian- lineages of ZIKV have different impacts on host immune response. We studied the pro-inflammatory and antiviral response of ZIKV-infected monocytes using publicly available RNA-seq analysis (GSE103114). We compared the transcriptomic profiles of human monocytes infected with ZIKV Puerto Rico strain (PRVABC59), American-Asian lineage, and ZIKV Nigeria strain (IBH30656), African lineage. We validated RNA-seq results by ELISA or RT-qPCR, in human monocytes infected with a clinical isolate of ZIKV from Colombia (American-Asian lineage), or with ZIKV from Dakar (African lineage). The transcriptomic analysis showed that ZIKV Puerto Rico strain promotes a higher pro-inflammatory response through TLR2 signaling and NF-kB activation and induces a strong IL27-dependent antiviral activity than ZIKV Nigeria strain. Furthermore, human monocytes are more susceptible to infection with ZIKV from Colombia than ZIKV from Dakar. Likewise, Colombian ZIKV isolate activated IL27 signaling and induced a robust antiviral response in an IFN-independent manner. Moreover, we show that treatment of monocytes with IL27 results in decreased release of ZIKV particles in a dose-dependent manner with an EC50 =2.870 ng/mL for ZIKV from Colombia and EC50 =10.23 ng/mL to ZIKV from Dakar. These findings highlight the differential inflam matory response and antiviral activity of monocytes infected with different lineages of ZIKV and may help better management of ZIKV-infected patients.